(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Students are able to co-construct information and enhance their writing talents to a larger extentthan they might if they were working independently as a consequence of the dependency that existsbetween them. It is vital to remind students that they can learn a lot from one other and that they should behappy to share what they know in order to enrich the educational experiences of everyone engaged. It isalso necessary to remind students that they should share what they know in order to enrich theeducational experiences of everyone involved. However, collaborative writing does not occur in avacuum, nor does it miraculously arise after only a few minutes of putting pen to paper. Rather, itrequires time and effort from several people. Writing in collaboration, just like any other kind of writing,is most successfully completed via consistent practise. In addition to this, it is something that requiresboth time and effort. Moreover, favorable effects are conceivable. Businesses all around the world haverecently come to the realization that collaborative writing may give greater results than the efforts ofindividual writers.